Development of geogebra-based interactive multimedia on triangle and quadrilateral topics to enhance students' understanding of mathematical concepts - Achmad Buchori; Noviana Dini Rahmawati; Milagros Baldemor (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Understanding mathematical concepts is essential for students, as it forms the basis for developing other mathematical abilities. Many students struggle with abstract mathematical ideas, particularly in geometry.Aim: This study aims to examine the validity, practicality, and effectiveness of GeoGebra-based interactive multimedia in enhancing students’ understanding of triangles and quadrilaterals.Method: This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The subjects involved were seventh-grade students at a junior high school. Validation of the product was conducted by two material experts and two media experts. Practicality was assessed using student response questionnaires, while effectiveness was measured through a quasi-experimental design involving a pretest-posttest control group. Data were analyzed using descriptive statistics and inferential analysis to determine the improvement in conceptual understanding.Result: Validation scores reached 88% (material) and 88.2% (media), indicating high validity. Student feedback showed positive responses toward the multimedia's usability and engagement. The experimental group outperformed the control group, with a higher average score, demonstrating the effectiveness of the developed multimedia.Conclusion: GeoGebra-based interactive multimedia is a valid, practical, and effective tool for improving students’ understanding of mathematical concepts, particularly in triangle and quadrilateral topics. Its integration into classroom instruction enhances engagement and supports meaningful learning experiences. Future research is recommended to investigate the long-term effects of such multimedia on students’ conceptual retention, its application to other mathematical domains and grade levels, and its integration with collaborative or inquiry-based learning approaches.